Higher habitual flavonoid intakes are associated with a lower risk of peripheral artery disease hospitalizations - Bondonno, Nicola P (Am J Clin Nutr, 2020)
BACKGROUND: The role of nutrition in the primary prevention of peripheral artery disease (PAD), the third leading cause of atherosclerotic cardiovascular disease, is undetermined. Flavonoids may attenuate atherosclerosis and therefore persons who consume flavonoid-rich foods may have a lower risk of developing PAD. OBJECTIVES: We aimed to examine the association between flavonoid intake and PAD hospitalizations and investigate if the association differs according to established risk factors for PAD. METHODS: Baseline data from 55,647 participants of the Danish Diet, Cancer, and Health Study without PAD, recruited from 1993 to 1997, were cross-linked with Danish nationwide registries. Flavonoid intake was calculated from FFQs using the Phenol-Explorer database. Associations were examined using multivariable-adjusted restricted cubic splines based on Cox proportional hazards models. RESULTS: After a median [IQR] follow-up time of 21 [20–22] y, 2131 participants had been hospitalized for any PAD. The association between total flavonoid intake and total PAD hospitalizations was nonlinear, reaching a plateau at ∼750–1000 mg/d. Compared with the median flavonoid intake in quintile 1 (174 mg/d), an intake of 1000 mg/d was associated with a 32% lower risk of any PAD hospitalization (HR: 0.68; 95% CI: 0.60, 0.77), a 26% lower risk of atherosclerosis (HR: 0.74; 95% CI: 0.62, 0.88), a 28% lower risk of an aneurysm (HR: 0.72; 95% CI: 0.59, 0.88), and a 47% lower risk of a hospitalization for other peripheral vascular disease (HR: 0.53; 95% CI: 0.42, 0.67). A higher total flavonoid intake was also significantly associated with a lower incidence of revascularization or endovascular surgery and lower extremity amputation. The association between total flavonoid intake and PAD hospitalizations differed according to baseline smoking status, alcohol intake, BMI, and diabetes status. CONCLUSIONS: Ensuring the adequate consumption of flavonoid-rich foods, particularly in subpopulations prone to the development of atherosclerosis, may be a key strategy to lower the risk of PAD.